Profil Kemampuan HOTS Siswa SMP Plus Ma’arif NU Ciamis pada Pelajaran Biologi - Fitria Pusparini; Lisna Mistiani (Bioed : Jurnal Pendidikan Biologi, 2023)
Education in 21st century is required to produce a generation that is skilled in applying technology and able to think critically. To achieve critical thinking skills can be through by HOTS questions. Against the background of the importance of students HOTS and demands of education in the 21st century, the purpose of this study was to describe students HOTS in class VIII science lessons at SMP Plus Ma'arif NU Ciamis. This research is a qualitative research with descriptive method. Data collected using observation, documentation, and interviews. The research subjects were science teachers and class VIII students at SMP Plus Ma'arif NU Ciamis. The results showed that the students HOTS on each cognitive dimension, the average score of students' critical thinking skills on the cognitive dimension of analyzing was 48%, then the percentage was 24% on the cognitive dimension of evaluating and creating by 28%. It can be concluded that the ability of class VIII students of SMP Plus Ma'arif NU Ciamis in solving science questions on the HOTS-oriented circulatory system material for each cognitive dimension is still in the poor category. The root cause of the problem is not only in student literacy but also in the teacher's ability to choose learning methods or models that can support and train students HOTS. One alternative solution to improve students HOTS abilities is the PBL model and microlearning.